The Influence Of Foreign Ownership, Stakeholder Pressure, And Profitability On Sustainability Report Disclosure - Ramadan, Sutan Saleh; Wijayanti, Anita (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This quantitative study aims to analyze the influence of foreign ownership, stakeholder pressure, and profitability on the sustainability report disclosure by companies listed on the LQ45 Index for the 2022–2024 period. The sustainability report disclosure was measured using the Sustainability Report Disclosure Index (SRDI), based on the Global Reporting Initiative (GRI) guidelines. The sample consists of 24 LQ45-indexed companies, resulting in 72 observation points. The results of the panel data regression indicate that foreign ownership positively and significantly influences sustainability report disclosure, whereas stakeholder pressure and profitability do not significantly affect it. However, those independent variables simultaneously influence sustainability report disclosure. These findings show that ownership structure, particularly foreign ownership, is a more dominant factor for sustainability transparency than stakeholder pressure and financial performance.